FDG-PET may predict the effectiveness of hyperbaric oxygen therapy in a patient with bisphosphonate-related osteonecrosis of the jaw: report of a case - Fatema, Chowdhury Nusrat; Sato, Jun; Yamazaki, Yutaka; Hata, Hironobu; Hattori, Naoya; Shiga, Tohru; Tamaki, Nagara; Kitagawa, Yoshimasa (Odontology, 2015)
We report an advanced case of bisphosphonate-related osteonecrosis of the jaw (BRONJ) in an osteoporotic patient treated with oral risedronate sodium for 2 years. An 80-year-old woman presented to our hospital complaining of pain, swelling and pus discharge in the lower alveolar ridge. Fluorine-18 labeled fluorodeoxyglucose positron emission tomography (FDG-PET) and bone scintigraphy showed definite uptake in the mandible. Under clinical diagnosis of BRONJ, we applied systematic treatments including antibiotic therapy, irrigation, cessation of bisphosphonate, hyperbaric oxygen (HBO) therapy, and debridement of necrotic bone. After pre-operative 20 sessions of HBO therapy, her clinical symptoms disappeared. SUV max of FDG-PET decreased definitely from 4.5 to 2.5, although magnetic resonance image and bone scintigraphy did not show remarkable changes. After minor surgery with debridement of necrotic bone, she received another ten sessions of HBO therapy. After the treatment, her clinical course was excellent. In conclusion, this report demonstrates FDG-PET may predict the effect of HBO therapy in BRONJ.